2023
DOI: 10.21037/atm-22-4284
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CaMK4 as a sex-difference-related gene in knee osteoarthritis

Abstract: Background: Osteoarthritis (OA) is a common degenerative joint disease with a higher prevalence in females than in males. Sex may be a key factor affecting the progression of OA. This study aimed to investigate critical sex-difference-related genes in patients with OA and confirm their potential roles in OA regulation.Methods: OA datasets GSE12021, GSE55457, and GSE36700 were downloaded from the Gene Expression Omnibus database to screen OA-causing genes that are differentially expressed in the two sexes.Cytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…To further investigate the role of CaMK4, OA was induced in mice by medial meniscal destabilization and the efficacy of early KN-93, a potent CaMK4 inhibitor, was evaluated. KN-93 administration was chondroprotective, further supporting the role of CaMK4 in OA ( 14 ). CaMK4 is an important member of the calmodulin-dependent kinase family known to be mainly distributed in the brain, thymus and bone marrow and not yet linked to musculoskeletal diseases.…”
Section: Finding Evidence-based Explanations For Gender Differences I...mentioning
confidence: 66%
See 2 more Smart Citations
“…To further investigate the role of CaMK4, OA was induced in mice by medial meniscal destabilization and the efficacy of early KN-93, a potent CaMK4 inhibitor, was evaluated. KN-93 administration was chondroprotective, further supporting the role of CaMK4 in OA ( 14 ). CaMK4 is an important member of the calmodulin-dependent kinase family known to be mainly distributed in the brain, thymus and bone marrow and not yet linked to musculoskeletal diseases.…”
Section: Finding Evidence-based Explanations For Gender Differences I...mentioning
confidence: 66%
“…A recent study by Feng et al screened some of the same datasets as previous studies for hub genes ( 14 ). The study confirmed previously identified genes including EGF, EGFR, CDC42, AQP4, and STAT 1 in addition to NTRK3 and CaMK4; neither NTRK3 nor CaMK4 have been previously linked to OA pathogenesis.…”
Section: Finding Evidence-based Explanations For Gender Differences I...mentioning
confidence: 99%
See 1 more Smart Citation
“…A study demonstrated that calmodulin-dependent protein kinase IV (CAMK4) is closely related to trophoblast function. It was also found that EGFR affects the activation of phospholipase C gamma 1 (PLCG1) and CAMK4 [24]. However, the role and mechanism of NUCB2/Nesfatin-1 in human placental syncytial disorder requires further study.…”
Section: Introductionmentioning
confidence: 99%